THE HISTORY OF INDONESIAN LEGAL SYSTEM IN THE DUTCH COLONIALIZATION ERA AND THE IMPACT ON ITS DEVELOPMENT - Arvifan Naufal Awang Budhiarta; Cindy Firdiani; Diyah Nur Aini Salsabila; Leoly Tubel Tsalsabila; Nicholas Marko Hasiando; Razkya Adisra Mulianto; Yediz Rantis Nababan (Problematika Hukum, 2022)
Indonesia, a country with a rich cultural and political history, has been influenced by various external factors throughout its existence, including Dutch colonialism. The impact of this era on the Indonesian legal system is evident in the legal structures and traditions that were put in place during this time. This research paper aims to provide a comprehensive analysis of the Indonesian legal system in the Dutch colonialization era and its development until the Reformation era. The analysis will cover the influence of local religious and cultural traditions, as well as the changes that have occurred in the Indonesian legal system since the end of the Dutch colonialization era. This research will include historical and legal perspectives, providing a nuanced understanding of the Indonesian legal system and its development during this period. This research aims to shed light on the various influences that have shaped the Indonesian legal system and to provide insights into the challenges faced and opportunities presented in the context of Dutch colonialism.Keywords: Indonesian Law; Dutch Law; Changes; Development.